Halal Tourism Development Through Creative Economy Of Local Communities In Sumbersuko District - Nur Farahim Kayfa; Siti Nur Latifah; Moch Mahsun; Nurhafid Ishari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the role of micro, small, and medium enterprises (MSMEs) and the creative economy in supporting the development of halal tourism in Sumbersuko District, Lumajang Regency. The research focuses on identifying the potential of MSMEs, the contribution of the creative economy to empowering local communities, as well as the supporting and inhibiting factors in the development of halal tourism. This study employs a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, documentation, and literature review. The research informants consist of MSME actors, tourism managers, and surrounding communities at two tourist destinations, namely Selokambang Natural Bath and Tumpak Selo Mini Tubing. The findings indicate that MSMEs play a strategic role in providing Muslim-friendly products and services, such as halal-certified culinary offerings and business services tailored to the needs of Muslim tourists. Community-based creative economic activities, including souvenir production and local product innovation, also enhance the attractiveness of halal tourism. However, several challenges remain, including increases in entrance ticket prices that affect visitor numbers, the lack of supporting halal tourism facilities, and fluctuations in tourist visits during certain periods. This study concludes that the development of halal tourism in Sumbersuko District requires synergy among MSMEs, creative economy actors, tourism managers, and local government. Such collaboration is essential to enhance halal product innovation, improve tourism facilities, and strengthen digital promotion in order to create a competitive, sustainable halal tourism destination that can improve the welfare of local communities.